Identification of novel putative adipomyokines by a cross-species annotation of secretomes and expression profiles. (20th October 2015) - Schering, Lisa; Hoene, Miriam; Kanzleiter, Timo; Jähnert, Markus; Wimmers, Klaus; Klaus, Susanne; Eckel, Jürgen; Weigert, Cora; Schürmann, Annette; Maak, Steffen; Jonas, Wenke; Sell, Henrike
Abstract: Adipose tissue and skeletal muscle are organs that respond strongly to obesity and physical activity exhibiting high secretory activity. To identify novel putative adipomyokines, comparative expression studies of skeletal muscle and adipose tissue of lean (C57BL/6J) and obese (C57BL/6J on a high-fat diet and NZO) mice, of sedentary and endurance trained C57BL/6J mice and of cattle characterized by different amounts of intramuscular fat were combined with human secretome data and scored. In highly regulated transcripts, we identified 119 myokines, 79 adipokines and 22 adipomyokines. Network analysis of these candidates revealed remodelling of extracellular matrix and tissue fibrosis as relevant functions of several of these candidates. Given the pathophysiogical relevance of fibrosis for adipose-muscle-cross-talk in obesity and type 2 diabetes and its physiological role in exercise adaptation and meat quality of farm animals, they represent interesting candidates for further investigations in different research areas and species.